2022
DOI: 10.26693/jmbs07.05.114
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic Analysis of N-Chlorotaurine Infusion Therapy in the Treatment of Patients with Peritonitis

Abstract: Peritonitis is the main cause of death in patients with acute surgical diseases of the abdominal cavity. The average mortality rate from disseminated forms is currently 30%. In complications of multiple organ failure and infectious-toxic shock, as well as in postoperative peritonitis in elderly patients, the lethality rate can reach 40%–70%. Thus, this disease is one of the most pressing medical, biological and economic problems of our time. The purpose of the study was to perform pharmacoeconomic analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Except for direct killing activity, after sublethal incubation, the compound also possesses a post-antibiotic effect and leads to loss of virulence in different pathogens, including yeasts. NCT was proved to be well tolerated by human tissue in clinical studies with instillation into the eyes, outer ear canal, nasal and paranasal sinuses, oral cavity and urinary bladder and skin ulcerations [7,8]. Lackner et al (2022) also demonstrated broad virucidal activity of NCT at pH 7.0 against viruses causing acute respiratory tract infections, including SARS-CoV-2, influenza viruses, and respiratory syncytial virus.…”
mentioning
confidence: 99%
“…Except for direct killing activity, after sublethal incubation, the compound also possesses a post-antibiotic effect and leads to loss of virulence in different pathogens, including yeasts. NCT was proved to be well tolerated by human tissue in clinical studies with instillation into the eyes, outer ear canal, nasal and paranasal sinuses, oral cavity and urinary bladder and skin ulcerations [7,8]. Lackner et al (2022) also demonstrated broad virucidal activity of NCT at pH 7.0 against viruses causing acute respiratory tract infections, including SARS-CoV-2, influenza viruses, and respiratory syncytial virus.…”
mentioning
confidence: 99%